Pengaruh Loan to Deposit Ratio, Kredit Macet dan Capital Adequacy Ratio Terhadap Profitabilitas Pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia Periode 2018-2020 - Erika Poniman; Jhon Raphael Saragih (Politeknik Ganesha Medan, 2022)
This study aims to describe the effect of Loan to Deposit Ratio, Bad Credit and Capital Adequacy Ratio on Profitability in Banking Companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The population in this study were 43 banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Sampling used purposive sampling method where samples were taken based on certain criteria. The sample is 23 banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The instrument used is documentation. The result of the study is that the Loan to Deposit Ratio has no effect on profitability in banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Bad Credit Affects Profitability in Banking Companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Capital Adequacy Ratio has no effect on profitability in banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Loan to Deposit Ratio, Bad Credit and Capital Adequacy Ratio have an effect on profitability in banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period..